2007
DOI: 10.1529/biophysj.107.104737
|View full text |Cite
|
Sign up to set email alerts
|

Nanopipette Delivery of Individual Molecules to Cellular Compartments for Single-Molecule Fluorescence Tracking

Abstract: We have developed a new method, using a nanopipette, for controlled voltage-driven delivery of individual fluorescently labeled probe molecules to the plasma membrane which we used for single-molecule fluorescence tracking (SMT). The advantages of the method are 1), application of the probe to predefined regions on the membrane; 2), release of only one or a few molecules onto the cell surface; 3), when combined with total internal reflection fluorescence microscopy, very low background due to unbound molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
91
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(92 citation statements)
references
References 46 publications
1
91
0
Order By: Relevance
“…Due to their high-aspect ratio geometry and exceptionally sharp tips, nanopipettes offer an important advantage over conventional nanopores as they can be easily adapted for use in single cell interrogation 15,16 and as a macroscopic delivery vehicle for intracellular injection. [17][18][19][20][21][22] . To date, delivery of molecules has so far only been quantified in close proximity to the tip by using fluorescence spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their high-aspect ratio geometry and exceptionally sharp tips, nanopipettes offer an important advantage over conventional nanopores as they can be easily adapted for use in single cell interrogation 15,16 and as a macroscopic delivery vehicle for intracellular injection. [17][18][19][20][21][22] . To date, delivery of molecules has so far only been quantified in close proximity to the tip by using fluorescence spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally fluorescence measurements have been very valuable in following the dynamics of delivery from nanopipettes and the behaviour of the fluorescent moieties while in a nanopipette [75,152]. These studies showed that it was possible to deliver a single fluorescent molecule to different subcellular regions of a boar spermatozoon and track the diffusion therein [152]. SICM has also been combined with scanning near field optical microscopy [153].…”
Section: (D) Scanning Electrochemical Microscopy-scanning Ion Conductmentioning
confidence: 99%
“…This enables controlled delivery of molecules onto a surface at defined positions, and by controlling the concentration of solution in the pipette and the applied voltage and dose time, delivery of individual molecules is possible [17 -20]. This has been used to study the diffusion of molecules over the surface of a boar sperm and probe the nature of the barrier between different macrodomains on the surface, when combined with single-molecule tracking, and is discussed in more detail below [21]. We have also trapped fluorophores in the tip of the pipette due to the force generated by dielectrophoresis (induced dipole forces) [22].…”
Section: Local Measurements Combined With Scanning Ion Conductance MImentioning
confidence: 99%